2004
DOI: 10.1179/crn.2004.020
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Smoothness of the Chewing Cycle Following Treatment of Anterior Crossbite Malocclusion: A Case Report

Abstract: This is a report of a case in which improvement in masticatory jaw movement kinematics occurred following orthodontic treatment. A patient who demonstrated a skeletal Class II jaw relationship, with anterior crossbite between the right upper and lower lateral incisors, underwent treatment with an edgewise appliance. The trajectories and smoothness of the patient's jaw-closing movement were compared before and after orthodontic treatment. The correction of the anterior crossbite allowed the patient to consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Such graphical representations of jerk‐cost may help clinical practitioners to visualize and better understand changes of smoothness in their patients’ mandibular movements during chewing. Previous studies reported evaluations of movement smoothness in mastication calculated jerk‐cost using normalized units of time and 3D pathway length (4–9); these methods were used to avoid introducing calculation errors through multiple differentiations. This normalization, however, prohibited the accurate measurement of the momentary jerk and jerk‐cost associated with discrete masticatory phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such graphical representations of jerk‐cost may help clinical practitioners to visualize and better understand changes of smoothness in their patients’ mandibular movements during chewing. Previous studies reported evaluations of movement smoothness in mastication calculated jerk‐cost using normalized units of time and 3D pathway length (4–9); these methods were used to avoid introducing calculation errors through multiple differentiations. This normalization, however, prohibited the accurate measurement of the momentary jerk and jerk‐cost associated with discrete masticatory phases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the utility of jerk‐cost measurements in the evaluation of masticatory movement and indicated a strong correlation between occlusal integrity and jerk‐cost (4). Other studies have shown that the jerk‐cost of the jaw movement during chewing is improved by the placement of prosthetic restorations (5, 6) and orthodontic treatments (7–9). It is expected, therefore, that the jerk‐cost as a measure of jaw movement smoothness may be used to evaluate the masticatory function of patients with tooth loss and malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…A normalisation technique that generates a measure of jerk cost, which is independent of movement duration ( T ) and amplitude ( D ) (NJC = jerk cost × T 5 / D 2 ), has been proposed. Indices such as NJC, movement time, peak velocity and symmetry of the velocity profile have proved to be effective in explaining the degree of the skilfulness of the human limb and jaw motions .…”
Section: Methodsmentioning
confidence: 99%
“…In general, a lower jerk cost indicates smooth movement having lesser tremulous motor segments inefficiently driven by rapid acceleration or deceleration. It has been reported that the kinematic parameters such as jerk cost and velocity profile indicate smoothness of jaw movements .…”
Section: Introductionmentioning
confidence: 99%
“…A recent case report 24 , using the current kinematic parameters, has documented improved masticatory jaw function as a result of progress in orthodontic treatment. In agreement with this, the morphologically improved occlusal state achieved as a result of orthodontic treatment was found to provide kinematically optimized masticatory jaw motion that was more skillful than that seen in individuals with untreated malocclusions.…”
Section: Discussionmentioning
confidence: 99%